Effect of incorporation of sugar palm (Arenga Pinnata [Wurmb] Merr.) fiber from various geographical regions towards the tensile and flexural properties of SPF/epoxy composites for engineering applications - S., M. Sapuan; M., M. Harussani (Wiley, 2022)
The objective of this study is to evaluate the tensile and flexural properties of epoxy composites reinforced with sugar palm (Arenga pinnata) fiber (SPF) harvested from various geographical locations, in Malaysia; Kuala Jempol, Negeri Sembilan (SPFN9); Benta, Pahang (SPFP); and Tawau, Sabah (SPFS), and from Java, Indonesia (SPFJ). Due to its optimal chemical composition, which includes a higher proportion of cellulose (44.53%), hemicellulose (10.01%) and lignin (41.97%), SPFN9/epoxy composites have the best tensile and flexural strength, according to this study, with 27.09 MPa and 54.44 MPa, respectively. The composites demonstrate slight decreases in the tensile strength (about 27–36%) and flexural strength (about 26%–42%) compared to the neat one. This is associated with the insufficient filling of the polymer amount. The hydrophilic characteristic of SPF makes it tough to bind to hydrophobic epoxy, creating a difficulty with interfacial adhesion between the filler and matrix. Thus, the SPF needed to be treated prior to the fabrication of composites to improve its mechanical properties for structural and automotive applications.